Kurzzeit - Jäger, Katrin; Köster, Katharina; Tempel, Tobias (Germany : HFF Münich, 2008)
Lizzy is 44. Her memory only lasts for a few minutes. She forgets where the supermarket is as soon as she is out on the street. She forgets how many cigarettes she has smoked. She forgets visiting her daughter, which she had been really looking forward to. A challenging view on the struggle to remember.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films